(untitled) (Iraqi Journal of Medical Sciences, 2021)
Background: Cervical radiculopathy (CR) is a pathological procedure that encompasses root of the cervical nerve. Cervical disc herniation, accompanied by cervical spondylosis, is among the most common causes of radiculopathy. Clinical neurophysiology is a medical field focused mainly on assessing activity in the nervous system and muscles being an expansion of neurological assessment, using particular same anatomical localization criteria as clinical testing. Objective: To evaluate the sensitivity and specificity of conduction time of the intraspinal segment of peripheral motor neurons in the diagnosis of CR using cervical root magnetic stimulation and conventional electromyography (EMG) study. Methods: Fifty patients (15 males and 35 females) aged 46.02±9.76 years with reported CR were subjected to an electrophysiological examination and control group consisted of 50 (36 females and 14 males) healthy volunteers aged 36.24±12.09 years. Analysis of sensory and motor nerve conduction, conventional needle EMG test, and motor evoked potentials (MEPs) for all (recording abductor pollicis brevis (APB), abductor digiti minimi (ADM), biceps brachii (BB), deltoid muscles) was conducted to determine the peripheral nerves, muscles, sensory and motor pathways. The motor evoked potential (MEP) parameters studied for the median, ulnar musculocutaneous and axillary nerves include latency of the spinal root peripheral motor conduction time (PMCT). Results: During direct cervical root stimulation, the PMCT of the median nerve shows the highest specificity (59%) than that of the ulnar nerve (57%), while the intraspinal latency shows the same specificity for both nerves (57%). In comparison, PMCT by kimura formula recording ADM during direct stimulation of the cervical root have the highest sensitivity (56%) than that of PMCT by kimura formula recording APB. Additionally, the recording of direct cervical root stimulation amplitude after deltoid muscle showed the highest specificity and sensitivity (57.0%, 58.0% respectively). On the other hand, PMCT shows the highest specificity and sensitivity while the BB muscle is recoded (62.0%, 49.0%). Conclusion: Overall, the current motor evoked potential study shows abnormalities in less than 60% of patients with cervical radiculopathy relative to conventional EMG needle study abnormalities that reached 90%. The intraspinal latency of the median and ulnar show low sensitivity and specificity. Keywords: Cervical radiculopathy, electromyography, motor evoked potentials Citation: Abdulhameed AK, Kaddori HG. Cervical intraspinal conduction time by magnetic root stimulation versus conventional electromyography in the diagnosis of cervical radiculopathy. Iraqi JMS. 2021; 19(1): 60-71. doi: 10.22578/IJMS.19.1.9